92 Clinical Frailty Scoring Is Crucial For the COVID-19 Era and Beyond. (16th March 2021) - White, L; Tyler, A; Samji, A
Abstract: Introduction: The COVID-19 pandemic placed a new focus on provision of clinical resources. With high mortality and limited capacity; appropriate decisions to escalate to critical care were vital for just resource allocation but also to prevent harm where interventions would not change outcomes. NICE guidance highlighted Clinical frailty scoring (CFS) as central to the decision-making process. 1, Despite initial criticism, recent evidence has confirmed increasing CFS as an independent risk factor to inpatient mortality in COVID-19.2 We conducted a quality improvement project with the aim of improving CFS documentation at the Royal Free Hospital. Methods: We reviewed the notes of 71 inpatients over the age of 65 years from 6 wards on 08/05/20–12/05/20 for both a CFS score documentation and clear treatment escalation plan at time points of initial clerking, post-take and following ward admission with an audit standard of 100%. We developed teaching sessions, promoted the CFS mobile application, developed a post-take sticker and an elderly medicine ward admission proforma. We re-audited 66 inpatient notes from the same 6 wards from 25/06/20–07/07/20. Results: Documentation.of CFS improved from 7% to 17% for clerking and post-take and from 13% to 24% on the ward admission. The number of patients with treatment escalation plans was 50%. Conclusion: CFS is crucial for the COVID-19 era and beyond. We have demonstrated that increased awareness improves use of CFS, though it is not yet being widely used in escalation decisions. 1. Covid-19 Rapid guideline: Critical Care in adults. NICE guideline [NG159]: https://www.nice.org.uk/guidance/ng159 Accessed July 2020 2. Hewitt J et al (2020): The effect of frailty on survival in patients with COVID -19 (COPE): a multicentre, European, observational cohort study; The Lancet: https://doi.org/10.1016/ S2468–2667(20)30146–8.